Characterization of potential CO2 emissions in agricultural areas using magnetic susceptibility - Leal, Fabio Tiraboschi [UNESP]; Coelho Franca, Ana Beatriz [UNESP]; Siqueira, Diego Silva [UNESP]; Teixeira, Daniel De Bortoli [UNESP]; Marques Junior, Jose [UNESP]; La Scala Junior, Newton [UNESP] (Univ Sao Paolo, 2015)
Soil CO2 emissions (fCO(2)) in agricultural areas have been widely studied in global climate change research, but its characterization and quantification are restricted to small areas. Because spatial and time variability affect emissions, tools need to be developed to predict fCO(2) for large areas. This study aimed to investigate soil magnetic susceptibility (MS) and its correlation with fCO(2) in an agricultural environment. The experiment was carried out on a Typic Eutrudox located in Guariba-SP, Brazil. Results showed that there was negative spatial correlation between fCO(2) and the magnetic susceptibility of Air Dried Soil (MSADS) up to 34.3 m distant. However, the fCO(2) had no significant correlation with MSADS, magnetic susceptibility of sand (MSSAND) nor clay (MSCLAY). However, MSADS could be a supplemental mean of identifying regions of high fCO(2) potential over large areas.
Keywords: magnetism; soil respiration; spatial variability; geostatistics